The Impact of Migration on the Family and Children’s Rights: Gendered Perspective - Winniefridah Matsa (Springer, Cham, 2023)
Absence of parents because of migration resulted in disintegration of the family unit and familial disruptions such as rise of new forms of families, shifting care and residence, new forms of care, disruption of child development and violation of rights. The chapter is grounded in family systems theory which postulates that changes in one element of the family as a system cause familial disruptions in the functioning of other parts of the family. Parental migration affects the composition of the demographic population and cause the fragmentation of the family unit and its functions of child upbringing and development. Although the family and the school are two separate systems, they are interdependent. What happens in one institution affects the other. This also leads to changes in parenting styles, interaction rules and boundaries for security and protection of children. This also results in violation of children’s rights. The impact depends to a greater extent on the nature of the change, the gender of the child and that of the caregiver.